THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND INTELLECTUAL INTELLIGENCE ON OCB WITH EMPLOYEE ENGAGEMENT AS AN INTERVENING VARIABLE - Karmila Karmila; Mawar Ratih Kusumawardani (SOSIOEDUKASI, 2025)
This research investigates how transformational leadership and intellectual intelligence influence Organizational Citizenship Behavior (OCB), incorporating employee engagement acting as an intervening variable within the Kediri Regency Department of Manpower. The investigation utilizes a quantitative methodology characterized by an explanatory framework. Data were obtained through questionnaires distributed to all employees using a census sampling technique. Path analysis was employed to assess encompassing both immediate and mediate associations among the variables. The findings suggest that transformational leadership exerts a favorable but non-significant impact on employee engagement, while intellectual intelligence demonstrates a constructive and substantial influence. Furthermore, transformational leadership negatively affects OCB, whereas intellectual intelligence and employee engagement both have positive and significant impacts. Employee engagement functions as a mediating variable that strengthens the effect of transformational leadership on OCB. These findings emphasize the need to enhance employee engagement through inspirational leadership and the development of intellectual competence to encourage OCB within public institutions.